Psychometric Properties of the Parental Alienation Scale - EAP - Paula Inez da Cunha Gomide; Claudia Nascimento Paleari; Pedro Afonso Cortez; Fernanda Otoni (Paidéia (Ribeirão Preto), 2025)
Abstract: Parental alienation is a phenomenon characterized by one parent engaging in behaviors that hinder and denigrate the other parent, thus affecting the child’s relationship with them. The purpose of this study was to evaluate the psychometric properties of the reformulated Parental Alienation Scale (PAS). The sample included 432 families involved in litigation, with information collected through an evaluator-administered interview script. Following data collection, the evaluator completed both the parent and child versions of the PAS. The parent version assessed three constructs: contact difficulties, exclusion of the other parent, and parenting behaviors during the assessment. The child version focused on behaviors related to rejecting the target parent and forming an alliance with the alienating parent. Results identified five factors in the parent version and two in the child version. The PAS provided evidence of content validity and internal consistency, supporting its use in assessing parental alienation in litigation cases.